THE IMPLEMENTATION OF EDUCATIONAL TOURISM DEVELOPMENT BY DINAS KEPEMUDAAN OLAHRAGA PARIWISATA DAN KEBUDAYAAN KABUPATEN PURWAKARTA : (A CASE STUDY OF PURWAKARTA MUSEUMS) - Marpaung, Melenia; Endah Trihayuningtyas; Mochamad Liga Suryadana (Politeknik Pariwisata NHI Bandung, 2022)
Purwakarta Regency tries to build tourism through educational tours that can be obtained from several museums. In the development of educational tourism in Purwakarta, it’s inseparable from the participation and involvement of the government as well as program plans in it. In looking at the things that have been done for the development of educational tourism, the implementation of existing programs and policies is needed. George C Edwards suggested that implementation can be seen from four things that are communication, resources, disposition and bureaucratic structure. This study focuses on these four things which aim to determine the implementation of the development of educational tourism in Purwakarta in terms of program alignment with the activities that have been made to its implementation. This research uses descriptive qualitative methods with data collection techniques in the form of documentation, observation and interviews. Data analysis with data reduction, data presentation, and drawing conclusions. The participants are employees in Dinas Kepemudaan Olahraga Pariwisata dan Kebudayaan Kabupaten Purwakarta as well as managers in each of its museums. The location of this study was at the Dinas Kepemudaan Olahraga Pariwisata dan Kebudayaan Kabupaten Purwakarta, taking additional data obtained from museums in Purwakarta, Diorama Nusantara, Diorama Purwakarta, Bale Indung Rahayu and Galeri Wayang. From the results of the research, it was found that communication was not optimal and there was no official cooperation between stakeholders, human resources were not facilitated with additional knowledge or training, the disposition had gone well enough, seeing in terms of bureaucratic structure there were no special policies governing educational tourism and the absence of SOPs or standard operational procedures which ultimately made it not run optimally development of educational tourism in Purwakarta. So it can be said that the development of educational tourism in Purwakarta has not gone according to what was expected.